Machine learning applied to banking supervision a literature review - Guerra, Pedro (2021)
Guerra, P., & Castelli, M. (2021). Machine learning applied to banking supervision a literature review. Risks, 9(7), 1-24. [136]. https://doi.org/10.3390/risks9070136